Regulasi Sistem Pendidikan Nasional Pada Masa Pandemi Covid-19 - HM. Rois; Untung Khoiruddin (Indonesian Journal of Humanities and Social Sciences, 2023)
The Indonesian people now need a process of national education regulation after the Covid-19 School/Madrasah/Islamic Boarding School Mataraman Region, arguing that the current institution must be able to provide attractive advantages or achievements to the wider community, so one of the advantages or achievements requires effort national education regulations. Therefore, with the impact of the post-pandemic Covid-19 on national education the School/Madrasah/Pesantren in the Mataraman Region was able to bring significant changes and developments in the era of globalization Thus, that the existence of education regulations after the Covid-19 pandemic, the Indonesian nation will soon avoid catastrophe and the plight of the world accompanied by intention to Allah SWT.